PERANCANGAN ALAT UJI IMPAK METODE CHARPY DAN IZOD - Fery Hardiana; Haris Budiman; Yudi Samantha (PROCEEDING STIMA)
Impact test is one method used to determine the strength, hardness and ductility of the material. Therefore the impact test is widely used in the field test the mechanical properties possessed by the material. Toughness (impact) is a materials resistance to shock loads. This is what distinguishes impact testing the tensile and hardness testing where loading is done slowly. Impact test is an attempt to simulate the material operating conditions frequently encountered in the transportation or construction equipment where the load does not always occur gradually but comes suddenly. The purpose of this paper is able to design and make tools charpy type impact test and Izod, knowing the mechanism of action, and analyze the performance of the tool at a time to recalibrate based on the impact energy of specimens. The methodology applied has three main points, namely the construction design, the manufacturing, construction and calculation. This impact test equipment has a capacity of 140 Joule, weight 20 kg pendulum, swinging point to point distance at 560 mm, the initial position beatings 105o and has dimension of length = 746,43 mm, width = 428,6 mm and 1221,85 mm high .Keywords: Design and construction calculations